A-train : memoirs of a Tuskegee Airman - Dryden, Charles W. (Charles Walter) (University of Alabama Press, 1997)
How does a black American prepare for a career in a profession traditionally closed to blacks? And how does he or she cope with the frustrations and dangers that subsequent experiences generate? A-Train is the story of one of the black Americans who, during World War II, graduated from Tuskegee Army Flying School and served as a pilot in the 99th Pursuit Squadron. Charles W. Dryden has prepared an honest, fast-paced, balanced, vividly written, and very personal account of what it was like to be a black soldier, and specifically a pilot, during World War II and the Korean War. Colonel Dryden's book commands our attention because it is a balanced account by an insightful man who enlisted in a segregated army and retired from an integrated air force. Dryden's account is poignant in illuminating the hurt inflicted by racism on even the most successful black people. As a member of that elite group of those young pilots who fought for their country overseas while being denied civil liberties at home, Dryden presents an eloquent memoir of the experiences he has shared and the changes he has witnessed.